Valence of emotions and moral decision-making: increased pleasantness to pleasant images and decreased unpleasantness to unpleasant images are associated with utilitarian choices in healthy adults - Carmona-Perera, Martina; Marti, Celia; Pérez-García, Miguel; Verdejo-García, Antonio (Frontiers in Human Neuroscience, 2013)
Moral decision-making is a key asset for humans’ integration in social contexts, and the way we decide about moral issues seems to be strongly influenced by emotions. For example, individuals with deficits in emotional processing tend to deliver more utilitarian choices (accepting an emotionally aversive action in favor of communitarian well-being). However, little is known about the association between emotional experience and moral-related patterns of choice. We investigated whether subjective reactivity to emotional stimuli, in terms of valence, arousal and dominance, is associated with moral decision-making in 95 healthy adults. They answered to a set of Moral and Non-moral dilemmas and assessed emotional experience in valence, arousal and dominance dimensions in response to Neutral, Pleasant, Unpleasant Non-moral, and Unpleasant Moral pictures. Results showed significant correlations between less unpleasantness to negative stimuli, more pleasantness to positive stimuli and higher proportion of utilitarian choices. We also found a positive association between higher arousal ratings to negative moral laden pictures and more utilitarian choices. Low dominance was associated with greater perceived difficulty over moral judgment. These behavioral results are in fitting with the proposed role of emotional experience in moral choice.